2007
DOI: 10.1038/sj.bjp.0707534
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐angiogenic properties of a sulindac analogue

Abstract: Background and purpose: Angiopoietins (Ang) are crucial for new blood vessel formation and exert their effects by acting on the Tie2 receptor. We have recently described a sulindac analogue 2-((1E,Z)-1-benzylidene-5-bromo-2-methyl-1H-inden-3-yl)acetic acid; termed C-18 from now onwards) that inhibits Tie2 receptor activity in kinase assays in vitro. Here, we have assessed the ability of C-18 to inhibit angiogenesis-related properties of endothelial cells and tested its selectivity for the Tie2 receptor. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
1
13
0
1
Order By: Relevance
“…Blockade of the Ang1/Tie2 and VEGF/VEGFR2 signaling pathways strengthened the anti-VEGF therapy efficacy on angiogenesis (33,34). In our study, we observed that 4-ISO-Tempo blocked the phosphorylation of Tie2 at Tyr 992 after stimulating Ang1 (200 ng/ml) for 30 min.…”
Section: Discussionsupporting
confidence: 52%
“…Blockade of the Ang1/Tie2 and VEGF/VEGFR2 signaling pathways strengthened the anti-VEGF therapy efficacy on angiogenesis (33,34). In our study, we observed that 4-ISO-Tempo blocked the phosphorylation of Tie2 at Tyr 992 after stimulating Ang1 (200 ng/ml) for 30 min.…”
Section: Discussionsupporting
confidence: 52%
“…Angiogenesis is a tightly regulated, multi-step process that involves endothelial cell proliferation, migration, alignment, tube formation, and organization into capillary structures (Pyriochou et al, 2007). Tissue engineering seeks to provide regenerated tissue architectures in vitro and create thick, highly vascularized, multi-functional tissues capable of replicating native structures (Tsuda et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The signal for ET-1 mRNA was most prominent and the signal for ETRA was relatively low as compared to the expression of VEGFR2, a maker of angiogenesis [12][13][14]. Combined blockage of ET receptors using classical ETRA and ETRB blockers did not affect baseline angiogenesis and the mRNA expression of the angiogenesis marker VEGFR2, whereas ETRA and ETRB mRNA expression were significantly decreased after combined ETRA/ETRB blockade.…”
Section: Discussionmentioning
confidence: 90%